Kinetic and isotherm studies of lead adsorption onto durian leaf powder / Zurhana Mat Hussin - Mat Hussin, Zurhana; Mahadi, Azwanis Sofea; Megat Hanafiah, Megat Ahmad Kamal (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
The feasibility of citric acid modified durian leaf (CADL) to remove Pb(II) from aqueous solution was evaluated. CADL was characterized by using a Fourier transform infrared (FTIR) spectrometer to determine the effect of chemical modification on the functional groups of CADL. Parameters investigated in this study were pH, CADL dosage, initial Pb(II) concentration and contact time. Pb(II) adsorption onto CADL was best described by the pseudo-second-order model. The maximum monolayer adsorption capacity determined from Langmuir isotherm model was 16.64 mg/g